Tari Joged Pingit dalam Perspektif Teologi Hindu - Putri, Desak Nyoman Sri Suyasning (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Joged Pingit is a sacred dance categorized as tari wali, performed exclusively at Pura Taman Limut in Desa Pakraman Pengosekan, Ubud. The dance is deeply connected to the spiritual legacy of Dang Hyang Nirartha and Ida Pedanda Sakti Magelung, who bequeathed the sacred gelungan (headdress) as a medium of divine presence. This study examines the theological meaning of Joged Pingit through the framework of Hindu theology, specifically the dimensions of tattwa (philosophical understanding), susila (ethical values), and acara (ritual practices). Using a qualitative method with observation, interviews, and descriptive-analytical interpretation, the study reveals three core theological meanings: (1) the cosmological meaning, representing the harmony between the macrocosm and microcosm through symbolic movements and ritual space; (2) the soteriological meaning, in which the dance acts as moksa karma—a path of liberation through selfless offering; and (3) the ethical-spiritual meaning, teaching self-control, purity of mind, devotion, and reverence toward divine and ancestral energies. Thus, Joged Pingit functions not only as a sacred performance but also as a medium for spiritual cultivation and the preservation of cosmic balance in Balinese Hindu society.